ASSOCIATION OF CONSANGUINITY WITH RECURRENT FOETAL LOSS - Irshad, Romana; Muhammad Adnan Rashid,; FAROOQ, Abeera (Journal of Ayub Medical College Abbottabad, 2024)
Background: Approximately 25% of all recognized pregnancies result in foetal loss. Women who will experience two consecutive foetal loss is less than 5%, while loss of three or more consecutive pregnancies in the first trimester, termed as Recurrent foetal loss (RFL), occurs in 1% of all pregnancies. RFL is often associated with cousin marriages. Keeping in view the social and psychological burden associated with RFL, it deems necessary to conduct further studies, to clear this ambiguity about the adverse effect of consanguinity on the foetal loss. The study was done with the objective to ascertain association of consanguinity with recurrent foetal loss. Methods: A total of 432 individual were recruited in this case control study (216 each in case and control groups) and was conducted at the Armed Forces Institute of Pathology (AFIP) Rawalpindi. The Cases consist of women having recurrent foetal loss while controls were women who do not experience recurrent foetal loss. Results: The Cases had mean parity level of 5.13 while controls 4.02. The difference in parity level of both cases and controls was statistically significant. The mean live births for all the participants were 2.35±1.915 ranging from 0-7. The cases had 0.72 mean live births while controls had 3.98 mean live births. The cases and controls were compared for consanguinity, i.e., if they had a blood relationship with their husbands. 67 (31.01%) of the cases had consanguinity while 62 (28.70%) of the controls had consanguinity. There was no statistically significant difference among cases and controls in terms of consanguinity. Conclusion: Although our study does not show any significant harmful effect of consanguinity on foetal outcome, however more in-depth research is required to look for genetic loci which are contributing to the causation of RFL, especially those inherited recessively, since homozygosity is increased in consanguinity.